Constraining Dynamic Sediment‐Discharge Relationships in Cold Environments: The Sediment‐Availability‐Transport (SAT) Model. Issue 10 (19th October 2021) - Zhang, Ting; Li, Dongfeng; Kettner, Albert J.; Zhou, Yinjun; Lu, Xixi
Abstract: Accelerated glacier‐snow‐permafrost erosion due to global warming amplifies the sediment availability in cold environments and affects the time‐varying suspended sediment concentration (SSC) and discharge ( Q ) relationship. Here, the sediment‐availability‐transport (SAT) model is proposed to simulate dynamic SSC‐ Q relationships by integrating the sediment availability coupled by thermal processes, fluvial processes and long‐term storage exhaustion into a sediment rating curve (SSC = a × Q b with a and b as fitting parameters). In the SAT‐model, increased sediment sources from glacier‐snow‐permafrost erosion are captured by changes in basin temperature, showing an exponential amplification of SSC when basin temperature increases. Enhanced fluvial erosion by the elevated water supply from rainfall and meltwater is captured by the factor of runoff surge, which results in a linear amplification of SSC. The SAT‐model is validated for the permafrost‐dominated Tuotuohe basin on Tibetan Plateau utilizing multi‐decadal daily SSC/ Q in‐situ observations (1985–2017). Results show that sediment rating curves for Tuotuohe display significant inter‐annual variations. The higher parameter‐ b in a warmer and wetter climate confirms the increased sediment availability due to the expanded erodible landscapes and gullying‐enhanced connectivity between channels and slopes. Through capturing such time‐varying sediment availability, the SAT‐model can robustly reproduce the long‐term evolution, seasonality, and various event‐scale hysteresis of SSC, including clockwise, counter‐clockwise, figure‐eight, counter‐figure‐eight, and more complex hysteresis loops. Overall, the SAT‐model can explain over 75% of long‐term SSC variance with stable performance under hydroclimate abrupt changes, outperforming the conventional and static sediment rating curve approach by 20%. The SAT‐model not only advances understanding of sediment transport mechanisms by integrating thermal‐ and fluvial‐erosion processes, but also provides a model framework to simulate and project future sediment loads in other cold basins. Key Points: Glacier‐snow‐permafrost melting elevates sediment availability by enlarging erodible landscapes and enhancing channel‐slope connectivity A sediment‐availability‐transport (SAT)‐model is developed to simulate dynamic suspended sediment concentration (SSC)‐discharge relations by integrating sediment availability controlled by thermal/fluvial processes The SAT‐model can robustly reproduce the long‐term evolution, seasonality and various event‐scale hysteresis of SSC for cold basins